2014
DOI: 10.1001/jama.2014.10924
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Older Patients With Hypercholesterolemia

Abstract: Ideally, treatment of hypercholesterolemia for patients at risk of ASCVD should start before they turn 80 years old. No RCT evidence exists to guide statin initiation after age 80 years. Decisions to use statins in older individuals are made individually and are not supported by high-quality evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 61 publications
1
91
0
11
Order By: Relevance
“…The decision to initiate a statin in a patient older than 80 years should be made on an individual basis and usually for secondary prevention in a patient with arteriosclerotic cardiovascular disease (ASCVD) and with a life expectancy of more than 5 years. 77,78 Figure. a Describes patients who are healthy in general with no or few comorbidities and functionally independent.…”
Section: Statinsmentioning
confidence: 99%
“…The decision to initiate a statin in a patient older than 80 years should be made on an individual basis and usually for secondary prevention in a patient with arteriosclerotic cardiovascular disease (ASCVD) and with a life expectancy of more than 5 years. 77,78 Figure. a Describes patients who are healthy in general with no or few comorbidities and functionally independent.…”
Section: Statinsmentioning
confidence: 99%
“…1,2 Despite this, the very elderly have the highest rate of statin use in the United States. 3 Given that few studies have investigated the use of statins among this population in a longitudinal manner by vascular disease, we set out to do so.…”
mentioning
confidence: 99%
“…Interestingly, their pre-planned subgroup analyses demonstrated that the increased risk of short-term mortality differed with respect to age-a higher mortality was associated with morphine use in patients ≤80 years of age, although after morphine administration, advanced age and frailty are factors related to higher mortality. Recently, there is growing evidence that medication effects could differ between younger and elderly patients (20)(21)(22). Although mechanisms that explain the difference in effects of morphine between young and elderly patients in Miró's article (14) remain unknown, it is necessary to remain aware that their conclusion should be applied in patients individually in terms of age or frailty.…”
Section: Editorialmentioning
confidence: 99%